1956
DOI: 10.1111/j.1550-7408.1956.tb02442.x
|View full text |Cite
|
Sign up to set email alerts
|

A Sugar‐Containing Basal Medium for Vitamin B12‐Assay with Euglena; Application to Body Fluids*

Abstract: SUMMARY. An improved assay of vitamin B12 is described. The z strain of Euglena gracilis, which grows more vigorously than the bacillaris strain previously used, is recommended. The pattern of B12 specificity of the two strains appears to be the same. A new medium containing sucrose, aspartic acid, glutamic acid, and glycine at pH 3.6 is well buffered and allows luxuriant growth. Vigorous utilization of sugar appears to depend on readily available nitrogen and a Krebs‐cycle component; these requirements are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
113
0

Year Published

1960
1960
1975
1975

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 415 publications
(113 citation statements)
references
References 18 publications
0
113
0
Order By: Relevance
“…This ineffectiveness has been confirmed by Bovarnick et al (4,5) who reported that chloramphenicol, even at 2 mg/ml, did not prevent the synthesis of NADP-linked triose phosphate dehydrogenase in regreening Euglena. This enzyme is apparently translated on 87S cytoplasmic ribosomes since its synthesis was completely prevented by 15 ,ug/ml of cycloheximide (5). The failure of chloramphenicol to inhibit cell division in Euglena suggests that protein synthesis on mitochondrial ribosomes is not prevented in vivo, possibly because mitochondria are impermeable to this inhibitor (5).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…This ineffectiveness has been confirmed by Bovarnick et al (4,5) who reported that chloramphenicol, even at 2 mg/ml, did not prevent the synthesis of NADP-linked triose phosphate dehydrogenase in regreening Euglena. This enzyme is apparently translated on 87S cytoplasmic ribosomes since its synthesis was completely prevented by 15 ,ug/ml of cycloheximide (5). The failure of chloramphenicol to inhibit cell division in Euglena suggests that protein synthesis on mitochondrial ribosomes is not prevented in vivo, possibly because mitochondria are impermeable to this inhibitor (5).…”
Section: Resultsmentioning
confidence: 98%
“…The D-threo-isomer of chloramphenicol was used exclusively throughout this work (8). The final concentration of inhibitors used was D-threo-chloramphenicol, 1 mg/ml; cyclohemixide, 15 ,g/ml; 5-fluorouracil, 5 mm; rifampicin, 250 ,ug/ml. All NaH'4C03 into acid-stable product was determined exactly as described previously (21).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Estimates of growth were made, after suitable dilution of cultures, by the method of Hutner, Bach & Ross (1956), by measuring the turbidity with a Klett-Summerson photoelectric colorimeter with a 66 (640-700 mp) filter. Photosynthetic pigments were routinely determined by extraction of euglenas with 3 x 5.0 ml.…”
Section: Introductionmentioning
confidence: 99%